Existence of quasi-equilibria on unbounded constraint sets. (1st February 2022) - Cotrina, John; Hantoute, Abderrahim; Svensson, Anton
ABSTRACT: A quasi-equilibrium problem is an equilibrium problem where the constraint set does depend on the reference point. It generalizes important problems such as quasi-variational inequalities and generalized Nash equilibrium problems. We study the existence of equilibria on unbounded sets under a coerciveness condition. We discuss the relation of our results with others from the literature.